Design, Fabrication And Experimental Evaluation Of Parabolic Trough Solar Concentrator At Bangi, Malaysia - Ibrahim Magaji Kotorkoshi
Solar thermal energy is one of' the potential sources of energy that compliments the fossil fuels for electricity and water heating system. Solar thermal collectors (STC) are among the costeffective systems of, this technology. The parabolic trough solar collector (PTC) is among the most promising technology of' solar thermal collector design. However, implementation of solar thermal system in tropical regions like Malaysia face challenges due to the characteristic nature of' the country that characterized by heavy rainfall, fönnation of clouds, occasional winds, varying temperatures and high humidity. Therefore, this study investigates the maximum thermal efficiency of' water heating system achieved from a simple solar thermal collector design under climatic conditions of Ban-i, Malaysia. The design used is parabolic trough solar collector of aperture area of 0.96 in embedded with automatic tracking system with aluminum toil reflecting material. Receiver of' the system was tested using copper and aluminum tube with difi'erent diameter, size and conditions (covered and uncovered). Experimental evaluation of water heating system was carried out under the static and flowing water conditions. Experimental results indicate that the automatic tracking PTC together with 2 cm aluminum and copper tube receivers performed adequately with an average thermal efficiencies of' 36 °o and 30 °o respectively. Results also indicate that the solar thermal system with automatic tracking together with smaller 1 cm diameter tube receiver enclosed inside a cover box achieves efficiency of 27 `%,. Most importantly, inexpensive parabolic trough reflector with low-cost design successfully used as water heating system up to temperature 100° C adequately under tropical climatic condition of Bangi, Malaysia.